Block periodization of endurance training - a systematic review and meta-analysis - Mølmen, K. S.; Øfsteng, S. J.; Rønnestad, B. R. (Open Access Journal of Sports Medicine, 2019)
Background: Block periodization (BP) has been proposed as an alternative to traditional (TRAD) organization of the annual training plan for endurance athletes. Objective: To our knowledge, this is the first meta-analysis to evaluate the effect BP of endurance training on endurance performance and factors determinative for endurance performance in trained- to well-trained athletes. Methods: The PubMed, SPORTdiscus and Web of Science databases were searched from inception to August 2019. Studies were included if the following criteria were met: 1) the study examined a block-periodized endurance training intervention; 2) the study had a one-, two or multiple group-, crossover- or case-study design; 3) the study assessed at least one key endurance variable before and after the intervention period. A total of 2905 studies were screened, where 20 records met the eligibility criteria. Methodological quality for each study was assessed using the PEDro scale. Six studies were pooled to perform meta-analysis for maximal oxygen uptake (VO2max) and maximal power output (Wmax) during an incremental exercise test to exhaustion. Due to a lower number of studies and heterogenous measurements, other performance measures were systematically reviewed. Results: The meta-analyses revealed small favorable effects for BP compared to TRAD regarding changes in VO2max (standardized mean difference, 0.40; 95% CI=0.02, 0.79) and Wmax (standardized mean difference, 0.28; 95% CI=0.01, 0.54). For changes in endurance performance and workload at different exercise thresholds BP generally revealed moderate- to large-effect sizes compared to TRAD. Conclusion: BP is an adequate, alternative training strategy to TRAD as evidenced by superior training effects on VO2max and Wmax in athletes. The reviewed studies show promising effects for BP of endurance training; however, these results must be considered with some caution due to small studies with generally low methodological quality (mean PEDro score =3.7/10).